The Importance of Knowledge Management Orientation Behavior and Innovation on Business Performance: a Lesson From Indonesia Creative Economy Sector - Hussein, Ananda Sabil (APMBA (Asia Pacific Management and Business Application), 2018)
Creative economy sector is considered as the emerging sector contributing significant percentage into emerging economy. For Indonesia, where the creative economy sector clasified as a pioneer sector by the government, business organization especially small medium enterprises are expected to have a good business performance. Knowledge management is one of determinants of business performance. However, some gaps are identified in literatures regarding the effect of knowledge management on business performance. This study uses one hundred self-administered questionnaires were distributed into the owner of SMEs in Indonesia creative economy sector. Partial Least Squares (PLS) was used to analyze the data. The statistical analysis showed that knowledge management orientation does not significantly affect business performance. However, this study found the significant effect of knowledge management orientation on innovation. Innovation was also found to be the significant predictor of business performance. Hence, it is determined that knowledge management orientation has an indirect effect on business performance through innovation. Upon the completion of this study, both theoretical and practical contributions were provided.